Health Promotion Strategy to Increase Cadre Knowledge about Stunting in the Work Area of the Puskesmas Krembangan Selatan: Strategi Promosi Kesehatan dalam Meningkatkan Pengetahuan Kader tentang Stunting Di Wilayah Kerja Puskesmas Krembangan Selatan - Yulia Yunara; Wahyu Agustin Eka Lestari; Retno Indarwati; Laila Mufida; Chandra Rahmadi; Wa Ode Dewi Hidayati; Rizal Fatkhur Rohman (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Stunting is a serious problem in Indonesia that has not been resolved, one of which is in the work area of the Krembangan Health Center where there are 25 toddlers who have stunting problems, one of the causes is the lack of knowledge of cadres about stunting problems in toddlers. So that an action is needed to increase public knowledge through health promotion activities. This health promotion is carried out by implementing community empowerment strategies through cadres. Objective: This community service activity aims to determine the effect of providing health promotion on stunting to health cadres. Methods: The data collection method in this study used pre-test and post-test questionnaires. The counseling method used is lecture, discussion and audiovisual where this audiovisual is in the form of a video containing material on stunting prevention. The number of respondents in this study were 20 people. Results: The results of the assessment showed that there was a difference in scores on the pre-test and post-test, namely the average score on the pretest was 8.2, while the score on the posttest showed that the average respondent was 9.55, there was an increase in value by 80%. Conclusion: Based on the counseling that has been carried out, it can be concluded that the knowledge and awareness of cadres about stunting has increased. This shows that health education is very important in overcoming health problems, especially the prevention of stunting. It is hoped that outreach activities on stunting prevention can be carried out sustainably with broader methods and targets such as creating social media groups with cadres as a forum to provide new information about stunting and as a medium for discussion.